Analisis Komposisi Board terhadap Firm Size Perusahaan Manufaktur yang terdaftar di BEI 2015 - Dewi Siswanti; Umi Muawanah (Sekolah Tinggi Teknik Malang, 2017)
This research aims to study the influence of board composition (BOC, BOD and AC) to the Firm Size on the manufacturing companies which are listed in Indonesia Stock Exchange. At 2015. Data source use secondary data which is accesed through Indonesia Stock Exchange, with sampling of 54 manufacturing companies in various sectors and sub sectors. With linear regression analysis, got reslut R-square 0,478, meaning between independent variable and dependent variable have (not significant) correlation equal to 47,8%. As an advanced analysis to further deepen the company’s position on board composition and firm size is used cluster analysis. As a result companies with high Firm Size are directly proportional to the large number of BOC and BOD, and enough with a moderate comiitee audit.